Development of a 3D model for the Leeuwpoort tin mine South Africa and the prediction of exploration success - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2020.